Foliar water uptake does not contribute to embolism repair in beech (Fagus sylvatica L.). (10th February 2022) - Schreel, Jeroen D M; Brodersen, Craig; De Schryver, Thomas; Dierick, Manuel; Rubinstein, Adriana; Dewettinck, Koen; Boone, Matthieu N; Van Hoorebeke, Luc; Steppe, Kathy
Abstract: Background and Aims: Foliar water uptake has recently been suggested as a possible mechanism for the restoration of hydraulically dysfunctional xylem vessels. In this paper we used a combination of ecophysiological measurements, X-ray microcomputed tomography and cryo-scanning electron microscopy during a drought treatment to fully evaluate this hypothesis. Key Results: Based on an assessment of these methods in beech ( Fagus sylvatica L.) seedlings we were able to (1) confirm an increase in the amount of hydraulically redistributed water absorbed by leaves when the soil water potential decreased, and (2) locate this redistributed water in hydraulically active vessels in the stem. However, (3) no embolism repair was observed irrespective of the organ under investigation (i.e. stem, petiole or leaf) or the intensity of drought. Conclusions: Our data provide evidence for a hydraulic pathway from the leaf surface to the stem xylem following a water potential gradient, but this pathway exists only in functional vessels and does not play a role in embolism repair for beech.